Biological Productivity and Nutrient Cycling in Pinus patula Plantations of Darjeeling Hills - Bhartari, S. K. (Indian Forester, 1986)
Estimate of dry matter production and cycling of nutrients in 4, 6, 8, 10, 12, and 14 year old plantation of Pinus patula in the darjeeling hills have been discussed. Total standing biomass ranges from 31.12 ton/ha to 125.97 ton/ha of which on an average 84.7% is contributed by above ground portion. Heighest concentration of all the nutrients is found to be in needle and least in wood. Concentration of nutrients in various plant parts except wood tends to decrease with age. On an average out of total uptake 49% N, 23% P, 35% K, 39% Ca and 46% Mg are returned to the soil through litter fall.